Koneksi Matematik Siswa SMP Melalui Pendekatan Contextual Teaching and Learning Melalui Model Kooperatif Tipe Think Pair Share - Pini Sulastri; Luvy Sylviana Zanthy (Journal on Education, 2019)
This study will look at differences in the ability of mathematical connections and self-regulated learning of junior high school students who obtain mathematics learning using the Contextual Teaching and Learning approach through the Cooperative Type Think Pair Share model, one of the causes of the low mathematical connection ability of students lies in the approach factor and the learning model when teaching. Based on the description of these problems, improvements can be made to improve students' mathematical connections with the Think Pair Share Cooperative Model. the population and sample in the study focused on eighth grade students, the method used in this study was a quasi-experimental method. Data collection techniques are by giving intrusion of learning and working on problems, then grouping grades based on the results of student performance in working on mathematical problems, arranged based on group distribution data to more specific value distribution into the mean median mode and graphs in order to know the results of applying the Type Cooperative model Think Pair Share is expected to improve students' mathematical connections.